1968
DOI: 10.1128/jb.95.5.1813-1827.1968
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Synthesis of Macromolecules During Amino Acid and Thymine Starvation in Bacillus subtilis

Abstract: Studies of Maal0e, Lark, and others with amino acidand thymine-starved cultures revealed successive steps in the biosynthesis of Escherichia coli chromosomes. In this study, the corresponding mechanisms in Bacillus subtilis 168 were examined. Using a strain requiring both thymine and tryptophan, we found that, 3 hr after the start of amino acid starvation, when the deoxyribonucleic acid (DNA) content of the culture had increased 40 to 50%, DNA synthesis ceased. After 4 to 5 hr, 100%o of the cells were immune t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1969
1969
1973
1973

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…There was no clear indication of localized wall thickening in the limited number of sections examined, and obviously further work is required including serial sectioning of cells with thickened walls. However, similar provisional results were obtained by Landman and colleagues (Miller et al 1967;Anraku & Landman, 1968) who observed an approximately twofold uniform thickening of walls of B. subtilis incubated in the presence of chloramphenicol. Studies in vivo (Chung, Hawirko & Isaac, 1964;Chung, 1967) have shown that growth in Bacillus cereus and Bacillus megaterium proceeds by the localized addition of new material to the existing wall.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…There was no clear indication of localized wall thickening in the limited number of sections examined, and obviously further work is required including serial sectioning of cells with thickened walls. However, similar provisional results were obtained by Landman and colleagues (Miller et al 1967;Anraku & Landman, 1968) who observed an approximately twofold uniform thickening of walls of B. subtilis incubated in the presence of chloramphenicol. Studies in vivo (Chung, Hawirko & Isaac, 1964;Chung, 1967) have shown that growth in Bacillus cereus and Bacillus megaterium proceeds by the localized addition of new material to the existing wall.…”
Section: Discussionsupporting
confidence: 84%
“…The reason for this limited synthesis is not known. Anraku & Landman (1968) reported that [32P]Pl incorporation into teichoic acid is strongly inhibited by chloramphenicol. Experimentally their procedures differed greatly from those we have used.…”
Section: Discussionmentioning
confidence: 99%
“…The ARCHER AND LANDMAN same experiment was performed with nonsynchronized cultures. Transformants for fu-r were scored on plates containing, in addition to the requirements of the strain, 1 ,ug of fu per ml. ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our results show clearly that chromosome replication is not essential for the development of competence since, in our cultures, competence first appears and develops long after DNA synthesis has been blocked. There is no net DNA synthesis in cultures of chromosome-arrested B. subtilis (3).…”
Section: Development Of Competence In Cultures Withmentioning
confidence: 97%
“…The procedure used for arrest of chromosomes at the terminus through amino acid starvation was previously published (3).…”
mentioning
confidence: 99%